Two new species of the genus Macromotettixoides Zheng, Wei & Jiang (Orthoptera: Tetrigidae: Metrodorinae) from China. (3rd April 2023) - Wei, Shi-Zhen; Deng, Wei-an
ABSTRACT: New species, Macromotettixoides daweishana sp. nov . from Yunnan and Macromotettixoides orthomargina sp. nov . from Sichuan, are described and illustrated. M. daweishana is similar to M. undulatifemura but differs in the shape of pronotum and narrow vertex. M. orthomargina is similar to M. shengtangshanensis but differs in the shape of infrascapular area and the wide vertex. The distribution and a key to the species of Macromotettixoides are given. http://www.zoobank.org/urn:lsid:zoobank.org:pub:38128DB6-2DFB-4C8B-9AD4-6B773B9EA8F3